Energiewende’s Lone Warriors: A Hyperlink Network Analysis of the German Energy Transition Discourse - Kaiser, Jonas (2016)
This paper explores the integration of different social fields within the German Energy Transition (Energiewende) discourse in the election year 2013 by analysing the hyperlink structures online. Energiewende describes the fundamental transition from non-renewable energy to sustainable sources. This goal is both ambitious and controversial. Numerous stakeholders try to make their voices and interests heard and as such politics has to both disseminate and collect information in order to include all relevant groups from different social fields in the political process. This discourse is also visible online. By analysing the hyperlink structures we are able to see the attention distribution of different actor groups in the network. This study shows that most actors tend to link within their own social field and do not aim for a more integrated public sphere. Especially political actors appear to be lone warriors who neither look left or right and mostly link within their own party and ignore other actors. Whereas social field as the media or public administration are relevant within the network we find that scientific actors are ignored by all fields, except for their own.